Behind the scenes of the British Library Qatar National Library Partnership: Digital operations and workflow management. Issue 2 (August 2018) - Davies, Richard; Alpanis, Sotirios
The British Library and Qatar National Library have been working in partnership since 2012 to make an extraordinary tranche of material available for everyone to access for free via the Qatar Digital Library. This article delves behind the scenes of the partnership, highlighting some of the operational and workflow lessons learnt when running this major digitisation programme. We look in detail at workflow management and coordination, how to use management information to find efficiencies, as well as providing a supportive team atmosphere for creative use of the collections via 'Hack Days'.